PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MELALUI PENDEKATAN KIMIA KONTEKSTUAL PADA MATERI KONSEP MOL - Hidayat, Aras; Rasmawan, Rahmat; Oktavianty, Erwina; Sutamah, Sutamah (Universitas Tanjungpura, 2024)
This research aimed to improve student engagement and learning outcomes in the subject of molecular concepts through the implementation of the contextual chemistry approach. The research was conducted using the Classroom Action Research (CAR) method with two cycles of action. The research subjects were students from Grade X Science 2 at SMA Negeri 6 Pontianak. Data were collected through observations of student activities and evaluation tests of learning outcomes. The results of the research showed a significant increase in student learning activities from Cycle I to Cycle II. The average increase in learning activities was 13.06%, and all aspects of activity met the criteria for active participation. Student learning outcomes also increased from Cycle I to Cycle II. The average learning outcomes increased from 69.71 to 75.14, and the percentage of mastery increased from 60% to 74.29%. The implementation of the contextual chemistry approach in teaching molecular concepts had a positive impact on student engagement and learning outcomes. Students demonstrated engagement in answering questions, presenting arguments, completing tasks, engaging in discussions, and presenting group work results. Its implementation can encourage student involvement in the learning process, improve conceptual understanding, and connect knowledge to everyday life situations